HACCP : a toolkit for implementation - Wareing, Peter (Royal Society of Chemistry, 2010)
Hazard Analysis and Critical Control Point (HACCP) is a systematic method to identify, evaluate and control food safety hazards. Since its initial development in the 1960s, HACCP has been increasingly used at every stage of the food chain. In many countries, it is a legal requirement for all food business operators to have some form of hazard analysis based on this system, and so there has been a growing interest in all aspects of HACCP. Leatherhead Food Research has, for many years now, offered a comprehensive food safety training programme. These training courses are now going to be complem.